Community's perspectives towards marine protected area in Perhentian Marine Park, Malaysia - Md. Nurul Islam, Gazi; Tai, Shzee Yew; Mohd Noh, Kusairi; Mohd Noh, Aswani Farhana (Scientific Research Publishing, 2014)
The Perhentian Islands located in the East coast of Peninsular Malaysia. They are well-known for their rich coral reef ecosystems. Marine resources of Malaysia have been overexploited in general due to overfishing and other development activities. Such no-take marine protected areas (MPAs) were established in Malaysia including Perhentian Islands Marine Park to enable overexploited marine resources to recover and to conserve coral reef ecosystems. This paper examines the current level of activities causing damages to the coral reef habitats in the Perhentian MPA. This study used paired comparison method to elicit the perception of the local stakeholders on the activities harmful to the marine habitats. The results of the analysis showed that various respondent groups had similar preference rankings on the harmful activities: littering, discarding fishing equipments, excess fishing and too many divers that cause damage to the habitats in the MPA area. The findings suggest that policy makers should take cognizance of the local stakeholders’ concern in planning and designing of marine protected areas in Malaysia.